A New Perspective on ISA-Equipment: Assistive devices for Drivers with Acquired Brain Injury - Klarborg, Brith; Lahrmann, Harry; Agerholm, Niels; Tradisauskas, Nerius; Harms, Lisbeth (Proceedings from the Annual Transport Conference at Aalborg University, 2007)
Intelligent Speed Adaptation [ISA] has proved successful at reducing the speed of normal drivers. However, until now the potential of ISA as an assistive device has been neglected. Two case studies were conducted to test ISA as a support for drivers with acquired brain injury [ABI] in driving with appropriate speed and thereby releasing cognitive capacity for other aspects of driving. The participants were two persons with ABI, who had retained their driving licenses. They were interviewed about their driving strategies before installation of ISA, and about their experience driving with ISA after the test period. The effect of ISA on the participants’ speed is analyzed and combined with their evaluation of the utility of ISA. The results suggest that with further customisation ISA may be a suitable “cognitive prosthesis” for drivers with ABI, but with some reservations towards certain cognitive deficits.